Between global consensus and local deviation: a critical approach on the universality of human rights, regional human rights systems, and cultural diversity - Kroetz, Flávia Saldanha (Revista de Investigações Constitucionais, 2016)
The global human rights regime, rooted in the Universal Declaration of Human Rights, nurtures a relatively uncontroversial consensus when it comes to the core principles and ideals of individual dignity and equality that stem from International Human Rights Law. Nonetheless, despite the longstanding and well-known debate concerning universalism versus cultural relativism, there still exists a thin and rather complex line between the universality of human rights on the one hand, and the respect for local practices and traditions on the other hand. This tension is further translated into the coexistence and overlapping between the universal and the regional systems for the protection of human rights, notably because the latter reflects an attempt to strengthen the protection of basic rights while underlining regional characteristics and common values shared by certain States, as opposed to an overarching, central scheme accused of overlooking the features of each region. Against this background, this brief research explores and, ultimately, rejects the claim that regional human rights systems hinder the successful protection and promotion of human rights at the regional level and undermine the effectiveness of the United Nations system.